Transvaginal Ultrasound‐Guided Biopsy of Deep Pelvic Masses: How We Do It. (18th April 2016) - Plett, Sara K.; Poder, Liina; Brooks, Rebecca A.; Morgan, Tara A.
Abstract : The purpose of this review is to discuss the rationale and indications for transvaginal ultrasound‐guided biopsy. Transvaginal ultrasound‐guided biopsy can be a helpful tool for diagnosis and treatment planning in the evaluation of pelvic masses, particularly when the anatomy precludes a transabdominal or posterior transgluteal percutaneous biopsy approach. A step‐by‐step summary of the technique with preprocedure and postprocedure considerations is included.